Introduction. Slavery and the Racialization of Humanity: Coordinates for a Comparative Analysis - Laura Menin (Antropologia, 2020)
This introduction provides some historical and conceptual coordinates for a comparative analysis of the multifarious ethnographic manifestations and performative powers of the “racial legacies” of slavery in contemporary contexts in West Africa, North Africa and the Middle East. What is the connection, if any, between current expressions of racism and historical experiences of slavery? How is “race”, with its relations with ideas of colour, origin and descent, locally conceptualized? How is “blackness” embodied and performed, experienced and contested, by different social actors – slave descendants, marginalized groups, sub-Saharan African migrants, students or professionals? In addressing these broad questions, this Special Issue radically expands the conversation on the legacies of slavery beyond the Sahara-Sahel, which has been the main focus of academic attention to date.